'A DESPERAT WEPON': RE-HAFTED SCYTHES AT SEDGEMOOR, IN WARFARE AND AT THE TOWER OF LONDON. (3rd December 2019) - Impey, Edward
Abstract : The Royal Armouries possesses two scythe blades of pre-mechanised manufacture, mounted axially on straight hafts to form weapons. An inventory of 1686 lists eighty-one scythe blades at the Tower of London (by 1694 described as booty captured from the Duke of Monmouth's rebels at Sedgemoor) and the surviving pair was probably among them. The Duke's shortage of standard-issue equipment made improvisation essential, and the choice of re-hafted scythe blades owed to their widespread, well known and effective use by irregular forces in Britain and Europe since the late Middle Ages. Monmouth's 'sithmen', some hundreds strong, took part in skirmishes and in the battle of Sedgemoor itself. Of interest to the Tower authorities as curiosities and for their propaganda value, the scythe blades were displayed, in diminishing numbers, from the seventeenth until the nineteenth century, and these two until the 1990s. In the future they will be displayed again, representing Monmouth's rebels and countless others, and a weapon type that deserves a greater level of study and recognition.